The ANGPTL8 rs2278426 (C/T) Polymorphism Is Associated with Prediabetes and Type 2 Diabetes in a Han Chinese Population in Hebei Province - Guangsen Hou; Yong Tang; Luping Ren; Yunpeng Guan; Xiaoyu Hou; Guangyao Song (International Journal of Endocrinology)
Background. Our aim was to investigate the association between the genetics of the angiopoietin protein-like 8 (ANGPTL8) rs2278426 (C/T) polymorphism with prediabetes (pre-DM) and type 2 diabetes (T2DM) in a Han Chinese population in Hebei Province, China. Methods. We enrolled 1,460 participants into this case-control study: healthy controls, n = 524; pre-DM, n = 460; and T2DM: n = 460. Ligase assays on blood samples from all participants were used to identify polymorphisms. Differences in genotype and allele distributions were compared by the chi-square test and one-way analysis of variance, and a post hoc pairwise analysis was performed using the Bonferroni test. The logistic regression technique was adjusted for age, sex, and body mass index. Results. The frequency of the TT (10.9%) genotype was significantly higher in pre-DM patients than in controls (odds ratio [OR] = 1.696, 95% confidence interval [CI] = 1.026–2.802, P=0.039). In the T2DM group, the CT (48%) and TT (15%) genotypes were significantly higher compared with those in the control group (CT : OR = 1.384, 95% CI = 1.013–1.890, P=0.041; TT : OR = 2.530, 95% CI = 1.476–4.334, P=0.001). The frequency of the T allele was significantly higher in the pre-DM (32.8%) and T2DM (39%) groups compared with the control group (26.9%) and was significantly associated with an increased risk of pre-DM (OR = 1.253, 95% CI = 1.017–1.544, P=0.034) and T2DM (OR = 1.518, 95% CI = 1.214–1.897, P=0.001). Furthermore, insulin levels in the pre-DM and T2DM groups were significantly decreased in those with the TT genotype compared with the CC and CT genotypes. Conclusion. ANGPTL8 rs2278426 may be involved in the mechanism of insulin secretion and could lead to an increased risk of pre-DM and T2DM.